UPAYA HUKUM BAGI PELAKU USAHA YANG TIDAK MENERIMA PUTUSAN KOMISI PENGAWAS PERSAINGAN USAHA DIBANDINGKAN DENGAN COMPETITION AND CONSUMER COMMISSION OF SINGAPORE - Hutami Fadliany Zakaria (2023)
KPPU is an independent institution that can be said to have a very broad jurisdiction, including the judiciary. Among the many powers possessed by the KPPU, there is one that clarifies the KPPU's position as an independent government institution with a judicial function, namely the power to make decisions and formulate decisions related to losses to other business owners or the general public. The research method applied is normative juridical, namely a research method that examines theories, concepts and legislation. This research will also discuss the implementation of decisions by the KPPU in cases of unfair business competition as well as a comparison of legal remedies carried out by business people if they do not accept the results of decisions from KPPU in Indonesia and CCCS in Singapore. The results found in this study are that the KPPU is not a judicial institution but a supervisory party to the implementation of Law no. 5 of 1999, so that the KPPU does not have the authority to be able to carry out the execution of its own decisions but must request an execution order against the District Court. If the entrepreneur rejects the KPPU's decision, an objection can be submitted to the District Court and an appeal to the Supreme Court. Meanwhile in Singapore, an objection can be submitted to the CAB. Those who can then submit an appeal to the High Court and cassation to the Court of Appeal.